6 categories of students to return to UMP in stages starting 6 March - Mimi Rabita, Abdul Wahit (2021)
KUANTAN, 5 February 2021 - Only six categories of students are allowed to return to the campus based on a pre-set schedule in ensuring the teaching and learning (T&L) activities can proceed effectively.